Mental health of cisgender and transgender during COVID-19 pandemic - Amitab Bhattacharjee; Asghar Afshar Jahanshahi; Mashiur Rahman Bhuiyan; Sakera Sultana (International Journal of Medical Research and Review, 2020)
Normally every individual wants to lead a free life movement but sometimes could not possible due to external environmental effects. During and after the home quarantine, people are still scared by consistent death and infected news of the 2019-nCoV pandemic. Which is why most of the persons have been feeling insecure and nervous that significantly growing up long term stress. The current study depicts the ongoing mental health condition of Bangladeshi cisgender and transgender individuals caused by the SARS-CoV-2 outbreak.Methods: A quarter-long cross-sectional survey has been conducted to observe the current mental health condition of the people in Bangladesh. The current study surveyed 1162 participants in the country. The DASS21 scale was used to measure the stress level of individuals.Outcomes: Results show that Bangladeshi individuals experienced a high level of stress (STD-15.28, Mean-32.61) that was higher than other recent studies such as China (STD: 5.45; Mean: 23.65). As a result, high levels of mental stress would be a reason for long-term mental illness after the 2019-nCoV pandemic, which may decline the health and working productivity. However, this study didn’t find any significant link between age/education levels and mental stress.Conclusion: The study findings disclosed that the growing up mental stress issue is holding a wide variety of people captive in its claws. Therefore, the study suggests that more studies on mental illness should be required in every region around the world. This may help to make experimental mental health recommendations and possible outlines for starting a healthy life after the COVID-19 pandemic.